2011
DOI: 10.6026/97320630005282
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic signature of Temporomandibular Joint Disorders (TMD): Toward diagnostically predictive biomarkers

Abstract: The temporomandibular joint (TMJ) articulates the mandible with the maxilla. Temporomandibular joint disorders (TMD) are dysfunctions of this joint, which range from acute to chronic inflammation, trauma and dislocations, developmental anomalies and neoplasia. TMD manifest as signs and symptoms that involve the surrounding muscles, ligaments, bones, synovial capsule, connective tissue, teeth and innervations proximal and distal to this joint. TMD induce proximal and distal, chronic and acute, dull or inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In our previous studies, we showed that TMD contributes to the development and exacerbation of cervical dystonia and other movement disorders, most likely via neuritis of the auriculotemporal branch of the trigeminal nerve that feeds into the pontine region and controls head and body posture [ 5 ]. In those studies we also proposed that the proteomic signature of biomarkers in local (e.g., joint synovial fluid) and distal body fluids (e.g., saliva, cerebrospinal fluid) in a translational research modality would behoove patient-targeted TMD diagnosis and prognosis [ 6 , 7 ]. Our data obtained within the EBD-PBRN also indicated remarkable elevations in certain neuroimmune factors in the synovial fluid of TMD patients that were significantly and positively correlated with diagnostic imaging-rated severity of the TMD condition [ 8 ] (Barkhordarian et al, under review) confirming the intimate coexistence of neuroimmunological and neuropathology complexities with TMD.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we showed that TMD contributes to the development and exacerbation of cervical dystonia and other movement disorders, most likely via neuritis of the auriculotemporal branch of the trigeminal nerve that feeds into the pontine region and controls head and body posture [ 5 ]. In those studies we also proposed that the proteomic signature of biomarkers in local (e.g., joint synovial fluid) and distal body fluids (e.g., saliva, cerebrospinal fluid) in a translational research modality would behoove patient-targeted TMD diagnosis and prognosis [ 6 , 7 ]. Our data obtained within the EBD-PBRN also indicated remarkable elevations in certain neuroimmune factors in the synovial fluid of TMD patients that were significantly and positively correlated with diagnostic imaging-rated severity of the TMD condition [ 8 ] (Barkhordarian et al, under review) confirming the intimate coexistence of neuroimmunological and neuropathology complexities with TMD.…”
Section: Introductionmentioning
confidence: 99%
“…The broad nature of these criteria leads to a significant risk of diagnostic failure [4,5]. Improved diagnosis by means of detailed translational research protocols (e.g., characterization of molecular profile of synovial inflammation -viz., by translational research protocols -is therefore timely and critical [6,7].…”
Section: Methodological Rationalementioning
confidence: 99%
“…Recent studies show that neurological disorders, such as Parkinson's Disease, Cervical Dystonia, Tourette's syndrome may have a root cause in TMJ related disorders. Undiagnosed TMJ disc dislocation such as distal condylar displacement and associated compression/irritation of the AT nerve may be due to bone loss, trauma, bruxism and other pathological etiologies [8,9]. Therefore, any neural interaction of the AT nerve can lead to a broad array of disorders such as neurologic, dystonic and neuromuscular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the anatomy of the trigeminal nerve, we see connections to the CNS and its sensory branches that innervate most visceral structures such as the lung, the gastrointestinal tract, heart and immune cell rich tissues and organs such as spleen and lymph nodes. Therefore, TMD symptoms can be local and specific, and or varied and systemic such as: comorbid neurological conditions, including cervical dystonia, Parkinson's disease, Tourette syndrome, Blepharospasm and complex regional pain syndrome (CRPS) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation